Practice of the anorexia nervosa and the autoesteem in pupils of the E.A.P. Infirmary and Psychology - UNHEVAL - 2009 - Fonseca-Livias, Abner A. (2019)
This study was realized to determine the influence of the practice of the anorexia and the autoesteem in the pupils of the E.A.P. of Inrmary and Psychology - UNHEVAL - 2009. The sample belonged 100 pupils. The study was of type correlacional, for the one that used the Descriptive - analytical, market method and according to the period of time it was of court trasversal. 96 % of the studied pupils is in risk of anorexia and alone 4 % suffers from anorexia. 80 % of the pupils has average autoesteem, 16 % has high autoesteem and only 4 % suffers from low autoesteem. To confirm the hypotheses Spearman's correlation was in use, with α 0.05, confidence level 95 % and 5 % of mistake. The value of r calculated is 0.061 and p 0.547 and this one is major that α 0.05, by what the hypothesis of investigation is rejected and the void hypothesis is accepted "The practice of anorexia does not relate to the autoesteem of the pupils who suffer it ".